Sistem Informasi Arus Kas Laboratorium Komputer Berbasis Web Dengan Teknologi Framework Modern - Lis Suryadi; Achmad Syarif; Mohamad Rafli Maulana (CV. Multi Kreasi Media, 2025)
Effective cash flow management serves as a fundamental pillar in the financial administration of computer laboratories, particularly those facing limited funds and high transaction volumes. This study seeks to develop a web-based cash flow information system employing modern frameworks such as Laravel and Vue.js. The system is designed to accurately record, monitor, and analyze financial transactions in real-time. Its purpose is to streamline financial reporting, enhance transparency, and reduce the likelihood of manual recording errors. The Software Development Life Cycle (SDLC) Waterfall model guides the system's development, with validation performed via black-box testing. The implementation demonstrates that the MVC architecture in Laravel and the use of Vue.js for the user interface offer significant flexibility and scalability for subsequent system enhancements. This research contributes to the digitalization of financial governance within educational institutions, leveraging open and easily deployable technology.